2017
DOI: 10.1002/etc.3915
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation kinetics, transformation, and toxicity prediction of ketoprofen, carprofen, and diclofenac acid in aqueous solutions

Abstract: Photodegradation of 3 commonly used nonsteroidal anti-inflammatory drugs, ketoprofen, carprofen, and diclofenac acid, was conducted under ultraviolet (UV) irradiation. The kinetic results showed that the 3 pharmaceuticals obeyed the first-order reaction with decreasing rate constants of 1.54 × 10 , 5.91 × 10 , and 7.78 × 10 s for carprofen, ketoprofen, and diclofenac acid, respectively. Moreover, the main transformation products were identified by ion-pair liquid-liquid extraction combined with injection port … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 41 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…UV irradiation at longer wavelength. There are some reports showing effects of the photodegradation on the biological activities of irradiated medicines [20][21][22][23][24]. In the case of naproxen, some photoproducts of it were more ecotoxic than naproxen, both in acute and chronic conditions [17,25].…”
Section: Structure Determination Of Naproxen Photoproductsmentioning
confidence: 99%
“…UV irradiation at longer wavelength. There are some reports showing effects of the photodegradation on the biological activities of irradiated medicines [20][21][22][23][24]. In the case of naproxen, some photoproducts of it were more ecotoxic than naproxen, both in acute and chronic conditions [17,25].…”
Section: Structure Determination Of Naproxen Photoproductsmentioning
confidence: 99%
“…Some organic compounds will decompose under certain natural light conditions. In an experiment of DCF irradiation by ultraviolet light, Li et al [23] found that six kinds of conversion products were produced. Some drugs have high degradation efficiency in the process of biodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth to be mentioned that decomposition compounds (A) and (C) are toxic free radicals (figure 4). 33 Benzodiazepine derivatives are used in therapy mainly as anxiolytics and are generally photolabile, but their degradation path depends on the structure of each derivative and on the degradation conditions. 34 A typical example of the photochemical reactivity of 1,4-benzodiazepines is the one of diazepam (7-chloro-1-methyl-5-phenyl-3H-1,4-benzodiazepin-2-one) decomposition (figure 5).…”
Section: Accepted Manuscriptmentioning
confidence: 99%